2018
DOI: 10.1016/j.genhosppsych.2017.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Illness burden and physical outcomes associated with collaborative care in patients with comorbid depressive disorder in chronic medical conditions: A systematic review and meta-analysis

Abstract: Objective Collaborative care (CC) improves depressive symptoms in people with comorbid depressive disorder in chronic medical conditions, but its effect on physical symptoms has not yet systematically been reviewed. This study aims to do so. Methods Systematic review and meta-analysis was conducted using Pubmed, the Cochrane Library, and the European and US Clinical Trial Registers. Eligible studies included randomized controlled trials (RCTs) of CC compared to care as usual (CAU), in primary care and general … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 87 publications
0
31
0
Order By: Relevance
“…The only outcomes affected by professional type were potential effects upon depression and increased respite service use from OT‐led case management in stroke (Hildebrand, 2015; Piersol et al., 2017) and reduced costs from inclusion of a pharmacist (Kane & Shamliyan, 2011). In team combinations, there were no differences upon illness burden or physical or mental health outcomes in collaborative care delivered by a case manager collaborating with a GP compared to one collaborating with a physician and psychiatrist in comparison to usual care (van Eck van der Sluijs et al., 2018). Likewise, replacing physician tasks with another healthcare professional showed some improvements in functioning, quality of life, costs and morbidity but had no clear patterns in team types and outcomes (Kane & Shamliyan, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The only outcomes affected by professional type were potential effects upon depression and increased respite service use from OT‐led case management in stroke (Hildebrand, 2015; Piersol et al., 2017) and reduced costs from inclusion of a pharmacist (Kane & Shamliyan, 2011). In team combinations, there were no differences upon illness burden or physical or mental health outcomes in collaborative care delivered by a case manager collaborating with a GP compared to one collaborating with a physician and psychiatrist in comparison to usual care (van Eck van der Sluijs et al., 2018). Likewise, replacing physician tasks with another healthcare professional showed some improvements in functioning, quality of life, costs and morbidity but had no clear patterns in team types and outcomes (Kane & Shamliyan, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…This did however limit our ability make clear recommendations about these components. Conclusions varied in their consistency across different LTCs (van Eck van der Sluijs et al., 2018; Ekers et al., 2013; Massimi et al., 2017).…”
Section: Limitationsmentioning
confidence: 99%
“…A multidisciplinary team (including general practitioners, nurses, specialists, and mental health professionals) coordinated by a case manager should closely collaborate to provide a wide range of interventions [e.g., patient education, psychological and pharmacological interventions, medication management, follow-up controls; National Collaborating Centre for Mental Health (UK), 2010 ]. This approach has been shown to be more effective than usual care as regards illness burden, physical, and psychological outcomes in patients with MDD and chronic diseases ( van Eck van der Sluijs et al, 2018 ). The first step to manage MDD in chronic diseases patients is the communication of the diagnosis as a step of the whole care process.…”
Section: Methodsmentioning
confidence: 99%
“…This approach has been shown to be more effective than usual care as regards illness burden, physical, and psychological outcomes in patients with MDD and chronic diseases (van Eck van der Sluijs et al, 2018). The first step to manage MDD in chronic diseases patients is the communication of the diagnosis as a step of the whole care process.…”
Section: Management Of Mdd In Chronic Diseases: the Multidisciplinarymentioning
confidence: 99%
“…Collaborative care programs have also expanded to include depressed patients diagnosed with chronic medical conditions given their high comorbidity among this population [50]. A recent meta-analysis found that collaborative care programs for depression and comorbid chronic medical conditions result in greater reductions in illness burden (d = 0.27) and depressive symptoms (d = 0.35) than treatment as usual, with improvements in physical outcomes observed for some, but not all, chronic health conditions (OR = 1.31-4.19) [51]. One of the largest primary care-based initiatives was the Care of Mental, Physical and Substance-use Syndromes (COMPASS) trial, a collaborative care program for patients with depression and comorbid diabetes and/or cardiovascular disease delivered in primary care clinics across eight states [52].…”
Section: Components Of Depression Treatment In the Pcmhmentioning
confidence: 99%